STRUCTURAL FEATURES OF THE ASSEMBLIES OF THE JOINING OF TRAM RAILS TO ROAD COVERAGE: Array - Kalmykov, O.; Hrybeniuk, S. (Municipal economy of cities. Series: «Economy science», 2021)
In the modern world, the priority is the development of clean urban electric transport. The constructive solutions used in the construction of the tram wheel in the past years are outdated and do not meet modern requirements. One of these problems is the destruction of asphalt coating in the places of road coverage to tram rails, which worsens the operational characteristics of tram crossings. The reasons for this problem can be attributed to the following: Not enough asphalt concrete near the rails; low adhesion of asphalt and metal from which rails are made; dynamic loads and vibrations arising from trams and motor transport; bad base of tram train and others. One of the options for increasing reliability and durability is to use as a road covering of tram plates. This solution is used in Ukraine and the European Union. German company RailBeton developed solutions for railway crossings - BetoCross. This system is a modular construction of reinforced concrete slabs, which are pulled together by steel strips. With the help of a system of fastenings and bearings, the flooring is fastened to rails, which provides vertical and horizontal stability of their position and stabilization under the influence of loading. To reduce the dynamic influence, the plates are based on reinforced concrete sleepers through the intermediate layers of the elastostomer. The load from the automobile transport is transferred to the broken beam. In addition to the positive features, the BetoCross system, due to the large number of connections, ties and bearings, requires frequent maintenance and maintenance. The Ukrainian state enterprise "Starokostiantyniv plant ZBSH" developed a similar technology, reinforced concrete plates with the help of a screw fastening through rubber gasket fixed to a special bridge type wallpaper. At a step of wallpaper 0,6 m the plate is attached to each wallpaper from two sides, with the length of the plate itself is 2,7 m. that is, on one plate there are five points of fastening on each side. Loads from the automobile transport, similar to the German technology, are transferred to the rubble balast and the basis. These technological solutions have found their application on railway crossings, and need some improvement for use in urban electric transport. The article reviews the constructive decision on the organization of the mentioned site, which is proposed by RS ENGINEERING in Kharkov. In the proposed solution instead of the crushed balast used monolithic reinforced concrete slab with supporting elements. The arising loads from the rolling stock and transport are transferred through the supporting elements to the concrete slab, which redistributes them on the rubble basis. As a road cover are used reinforced concrete plates covering RS-Slab. The plates are divided into 3 types: Road, interroad and external, which in turn have several sizes. The plates are bound to the supporting elements by means of screws in four points. To reduce dynamic influence between the film and the reference element, a rubber elastomer is laid. Depending on the size of the plates have different number of cutting sites. Also because of the design features possible option when the slab simultaneously relies not on all the supporting sites, these options should be taken into account when calculating the scale and choosing a class of concrete. This solution allows to solve the problems of road surface destruction on the side of the rails, keeps more load from transport, compared to asphalt. At the same time, there are factors that need to be studied in detail when designing and before implementing the solution in mass production. These include: Investigation of the influence of violation of standard assembly plates on the stress-deformed state of the element; determination of thickness and acceptable physical characteristics of the gasket on the plate supports; detailed development of a node for fixing plates. The use of reinforced concrete plates as a road coating has a number of advantages before asphalt concrete: Resistance to destruction on the rails; installation regardless of weather and temperature conditions; resistance to loads from trucks. At the same time, this decision has certain peculiarities that require detailed study, which is a branch of further research.